Formal Transformation in Urban Context Analytical Study to the Formal Transformation in Urban Context By using the remote sensing - Wahda Shuker Al-Hinkawi; Maha Haki Haki (Iraqi Journal of Architecture and Planning, 2009)
Many researchers interest directed to study the urban context as one of important concept toachieve temporal and spatial continuity in urban environment and link ihe buirding withneighboring.The paper deals with urban context as:-integral contain apposes crear orders and also statue procedurar definition it is containof potential and outstanding orders which instituted fiom joined parts in urban fabric,linked together in potential relations and bear urban and cutturai values posses formalconduct, coinciding functiiinal and rotating and bear association deliberaiive meaningsthe potential in shared between the parte and the whole and the outstanaing in rorm"al properties and vision for elements which undergo for natural ani coactivetransformation on the two dimensional and three dimeniional level,The outstanding order represents visual formal for urban contexl and the porential orderrepresented in whole and partial syntax properties behind visible phenomena.The research confirm upon studying the transformation in formal properties within the urbancontext by subtract ideas, studies of translormation in formal properties on the level of thewhole or part within the urban context, with this prospective t-he paper problem determinedas: " There is no obvious conception about transformation nature in formal properties ofurban context "-The paper hypothesis" the transformation in formal properties within the urban contextat the level of whole causes the format transformation in properties at the level of parts," was tested in real urban context represent by Ancient Damascus cit-v- in syria u, on. tf th.important urbanite and heritage element which has different type of .ont.it and it crouch toeconorric ,society and physics conditions.The formal indicators was defined and measured b1'using (cls) techniques in dra*,ings andAnalyzing visual and link formal properties on the level of the whole or part, the paperconcluded that deforming transformation in urban context may cause the transflrmation in ihecontext identity but it alio achieve formal homogeneity and prevenr the urban chaos, rvhenurban gradual growth and translormation md1 cause formal hetcrogeneity if building roleswas not controlling the transformation process and organize the. the urban mix betwein oldand new buildings.